2002
DOI: 10.1046/j.1529-8817.2002.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INVOLVEMENT OF A PLASMA MEMBRANE H+‐ATPase IN THE BLUE‐LIGHT ENHANCEMENT OF PHOTOSYNTHESIS IN LAMINARIA DIGITATA (PHAEOPHYTA)1

Abstract: Many brown algae, including the kelp Laminaria digitata (Huds.) Lamour., exhibit enhanced photosynthesis when they are given a small amount of blue‐light in addition to a background of saturating red light. This blue light effect is correlated with an increased uptake of carbon. In the present study, we tested the hypothesis that blue light acts by increasing the activity of a plasma membrane H+‐ATPase, thereby promoting an active carbon uptake across the plasma membrane. Photosynthetic carbon uptake was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It has been further shown that stimulation of photosynthesis of brown algae by blue light is correlated with an increased inorganic carbon uptake (Klenell et al 2002(Klenell et al , 2004Dring 1993a, b, 1996a, b;Schmid et al 1996). The degree of blue light stimulation is absolutely dependent on the CO 2 concentration of the medium (Forster and Dring 1992).…”
Section: Discussionmentioning
confidence: 99%
“…It has been further shown that stimulation of photosynthesis of brown algae by blue light is correlated with an increased inorganic carbon uptake (Klenell et al 2002(Klenell et al , 2004Dring 1993a, b, 1996a, b;Schmid et al 1996). The degree of blue light stimulation is absolutely dependent on the CO 2 concentration of the medium (Forster and Dring 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that low levels of UVR can enhance CO 2 acquisition in the diatom Skeletonema costatum by stimulating the extracelluar (periplasmic) carbonic anhydrase (data not shown). Blue light was demonstrated to increase the activity of plasma membrane H 1 -ATPase in a brown alga, Laminaria digitata (Klenell et al, 2002). UV-A, as a neighboring radiation of blue light, may serve a similar function and accelerate CO 2 acquisition and fixation.…”
mentioning
confidence: 99%
“…(Axelsson et al, 2000;Klenell et al, 2002Klenell et al, , 2004Mercado et al, 2006) and other macrophytes (Price & Badger, 1985;Hellblom et al, 2001;Hellblom & Axelsson, 2003;Uku et al, 2005). That is, a proton-gradient-driven CO 2 pump in the cell membrane based on the proton extrusion forming low pH (acid zones) on the thalli surface is integrated with HCO À 3 dehydration via external CA activity.…”
mentioning
confidence: 99%